2015
DOI: 10.1016/j.ejvs.2014.11.004
|View full text |Cite|
|
Sign up to set email alerts
|

Risk of Early Recurrent Stroke in Symptomatic Carotid Stenosis

Abstract: The data suggest that the early risk of recurrent stroke in symptomatic significant carotid stenosis is not as high as some earlier studies have shown. The risk is similar to several studies in which a modern medical treatment regime could be assumed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 33 publications
(18 reference statements)
2
27
1
1
Order By: Relevance
“…Previous studies have shown that stroke patients are at increased risk for a recurrent stroke compared to patients with an (ocular) TIA [8,9,10]. The results from the present study suggest that differences between adventitial microvasculature of symptomatic patients with (ocular) TIA and minor stroke might exist between these 2 groups.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…Previous studies have shown that stroke patients are at increased risk for a recurrent stroke compared to patients with an (ocular) TIA [8,9,10]. The results from the present study suggest that differences between adventitial microvasculature of symptomatic patients with (ocular) TIA and minor stroke might exist between these 2 groups.…”
Section: Discussionsupporting
confidence: 46%
“…The risk for a recurrent stroke within 7 days was 5.2% after a TIA versus 11.5% after a stroke [8]. Additional research showed that patients with a minor stroke have an increased risk for a recurrent stroke compared to patients with a recent TIA or ocular TIA (also known as amaurosis fugax) [9]. Data from the European Carotid Surgery Trial also showed that the hazard ratio for a 5-year risk of ipsilateral ischemic stroke depends on the type of the presenting cerebrovascular event [10].…”
Section: Introductionmentioning
confidence: 99%
“…5 In a recent Swedish study, Stromberg reported that 72% of their cohort of patients who presented with a TIA/minor stroke and a 50e99% stenosis were admitted on the day of the referring neurological event. 17 Thereafter, 2% suffered a stroke within 48 hours of their presenting symptom, increasing to 4% at 7 days. When 'strokes in evolution' were included, 3.2% of patients had suffered a stroke within 48 hours.…”
Section: Discussionmentioning
confidence: 99%
“…According to the ethical committee, a consent from the patient is not necessary in this type of retrospective study. Study patients were identified through the Western region Initiative to Gather information on Atherosclerosis database 8. All patients in this study had undergone US between October 1, 2004 and December 31, 2010 at Sahlgrenska University Hospital in Gothenburg and were given the International Classification of Diseases (ICD) code G45.3 (AF) as registered at The National Board of Health and Welfare in Sweden within 6 months prior to the US.…”
Section: Methodsmentioning
confidence: 99%